2005
DOI: 10.5194/acp-5-1423-2005
|View full text |Cite
|
Sign up to set email alerts
|

Ozone loss derived from balloon-borne tracer measurements in the 1999/2000 Arctic winter

Abstract: Abstract. Balloon-borne measurements of CFC11 (from the DIRAC in situ gas chromatograph and the DESCARTES grab sampler), ClO and O 3 were made during the 1999/2000 Arctic winter as part of the SOLVE-THESEO 2000 campaign, based in Kiruna (Sweden). Here we present the CFC-11 data from nine flights and compare them first with data from other instruments which flew during the campaign and then with the vertical distributions calculated by the SLIM-CAT 3D CTM. We calculate ozone loss inside the Arctic vortex betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…However, its has been shown that compact tracer-tracer relations can be simulated for the polar vortex by Eulerian chemical transport models (Plumb et al, 2000). Recently (Robinson et al, 2005) reported simulations with the SLIMCAT model, showing compact ozone/CFC-11 relations in agreement with balloonborne measurements.…”
Section: Three-dimensional Chemistry Transport Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its has been shown that compact tracer-tracer relations can be simulated for the polar vortex by Eulerian chemical transport models (Plumb et al, 2000). Recently (Robinson et al, 2005) reported simulations with the SLIMCAT model, showing compact ozone/CFC-11 relations in agreement with balloonborne measurements.…”
Section: Three-dimensional Chemistry Transport Modelsmentioning
confidence: 99%
“…Measurements from aircraft (Proffitt et al, 1990(Proffitt et al, , 1993Richard et al, 2001;Ross et al, 2004;Ulanovskii et al, 2004), satellites (Müller et al, 1996;Tilmes et al, 2003bTilmes et al, , 2004, balloons (Müller et al, 2001;Salawitch et al, 2002;Vogel et al, 2003;Robinson et al, 2005), and from the Space Shuttle (Michelsen et al, 1998) were used for such analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tracer-tracer correlations (TRAC) have been used, for more than a decade now, to quantify chemical ozone loss in the polar vortices. Measurements from aircraft (Proffitt et al, 1990(Proffitt et al, , 1993Richard et al, 2001;Ross et al, 2004;Ulanovskii et al, 2004), satellites (Müller et al, 1996;Tilmes et al, 2003bTilmes et al, , 2004, balloons (Müller et al, 2001;Salawitch et al, 2002;Vogel et al, 2003;Robinson et al, 2005), and from the Space Shuttle (Michelsen et al, 1998) were used for such analyses.…”
Section: Introductionmentioning
confidence: 99%
“…It is well suited for long periods of unattended operation. Earlier versions have been deployed on balloons, at ground-based sites and on aircraft (Robinson et al, , 2005Ross et al, 2004). The GC has a modular design with an adsorbent tube containing ∼1 mg each of Carboxen 1016 and 1001, which removes the target halocarbons from the air.…”
Section: The µ-Dirac Gas Chromatographmentioning
confidence: 99%